PENINGKATAN PENGETAHUAN TENTANG KETERAMPILAN SADARI DI KELURAHAN PASIR KIDUL KABUPATEN BANYUMAS - Ulfah, Mariah; Adriani, Prasanti (Dinamika Journal : Pengabdian Masyarakat, 2019)
Based on Riskesdas data, the prevalence of tumors / cancer in Indonesia shows an increase from 1.4 per 1000 population in 2013 to 1.79 per 1000 population in 2018. For the prevention and control of cancer in Indonesia, especially the two most types of cancers in Indonesia, namely cancer breast and cervix, the government has made various efforts including early detection of breast cancer and cervical cancer in women aged 30-50 years using the Clinical Breast Examination (SADANIS) method or Self Breast Examination (SADARI). The problem of breast examination should be done alone as an initial screening. Members of Dawis Mawar 3 are women of reproductive age, where of the 25 members there have been incidents of 2 people suffering from breast tumors and 1 person with enlargement in the armpit gland, but the condition makes 1 person visit an alternative clinic. Therefore, we are interested in doing community service about the importance of BSE training in Pasir Kidul Subdistrict, West Purwokerto. Keywords: Breast cancer, breast self-exam, cadre